Vitamin A deficiency and vitamin A supplementation affect innate and T cell immune responses to rotavirus A infection in a conventional sow model - Chepngeno, Juliet; Amimo, Joshua O.; Michael, Husheem; Raev, Sergei A.; Jung, Kwonil; Lee, Marcia V.; Damtie, Debasu; Omwando, Alfred; Vlasova, Anastasia N.; Saif, Linda J. (Frontiers in Immunology, 2023)
Rotavirus A (RVA) causes 200,000 diarrheal deaths annually in children <5yrs, mostly in low- and middle-income countries. Risk factors include nutritional status, social factors, breastfeeding status, and immunodeficiency. We evaluated the effects of vitamin A (VA) deficiency/VA supplementation and RVA exposure (anamnestic) on innate and T cell immune responses in RVA seropositive pregnant and lactating sows and passive protection of their piglets post-RVA challenge. Sows were fed VA deficient (VAD) or sufficient (VAS) diets starting at gestation day (GD)30. A subset of VAD sows received VA supplementation from GD|76 (30,000IU/day, VAD+VA). Sows (6 groups) were inoculated with porcine RVA G5P[7] (OSU strain) or Minimal Essential Medium (mock) at GD 90: VAD+RVA; VAS+RVA; VAD+VA+RVA; VAD-mock; VAS-mock; and VAD+VA-mock. Blood, milk, and gut-associated tissues were collected from sows at several time points to examine innate [natural killer (NK), dendritic (DC) cells], T cell responses and changes in genes involved in the gut-mammary gland (MG)-immunological axis trafficking. Clinical signs of RVA were evaluated post inoculation of sows and post-challenge of piglets. We observed decreased frequencies of NK cells, total and MHCII+ plasmacytoid DCs, conventional DCs, CD103+ DCs and CD4+/CD8+ and T regulatory cells (Tregs) and NK cell activity in VAD+RVA sows. Polymeric Ig receptor and retinoic acid receptor alpha (RARα) genes were downregulated in mesenteric lymph nodes and ileum of VAD+RVA sows. Interestingly, RVA-specific IFN-γ producing CD4+/CD8+ T cells were increased in VAD-Mock sows, coinciding with increased IL-22 suggesting inflammation in these sows. VA supplementation to VAD+RVA sows restored frequencies of NK cells and pDCs, and NK activity, but not tissue cDCs and blood Tregs. In conclusion, similar to our recent observations of decreased B cell responses in VAD sows that led to decreased passive immune protection of their piglets, VAD impaired innate and T cell responses in sows, while VA supplementation to VAD sows restored some, but not all responses. Our data reiterate the importance of maintaining adequate VA levels and RVA immunization in pregnant and lactating mothers to achieve optimal immune responses, efficient function of the gut-MG-immune cell-axis and to improve passive protection of their piglets.